Synthesis, Antibacterial and Antifungal Activities of s Derivatives - B. B. Baldaniya; P. K. Patel (E-Journal of Chemistry)
Several Nʹ-{4-[(3-chloro-4-fluorophenyl) amino]-6-[(-aryl) amino] -1, 3, 5-triazin-2-yl} isonicotinohydrazides (6a-r) and N2-(Aryl)-N4, N6-dipyrimidin-2-yl-1,3,5-triazine-2,4,6-triamines (4a-o) were prepared. All newly synthesized compounds have been tested for their antibacterial activity against gram (+)ve and gram (-)ve bacteria and also on different strains of fungi. Introduction of -OH, -OCH3, -NO2, -Cl and -Br groups to the heterocyclic frame work enhanced antibacterial and antifungal activities.